Students’ Perspectives of Social Media As Medium of Learning English - Fanalisa Elfa; Rindilla Antika (International ABEC, 2022)
This major aim of this study is to seek for better understanding of students’ perceptions towards using social media for learning English. This study also attempts to identify the most frequently used social media in English learning. The participants of this study were 78 students of State Polytechnic of Bengkalis who had used social media as English learning medium. The data were collected through questionnaire distributed by using google forms. The results of this study showed that the students had positive attitudes towards the utilization of social media for learning English. The finding of the study also revealed that the most frequent social media used for learning English is YouTube and WhatsApp as the most frequent media used for general purposes. It can be concluded that using social media in English learning has positive impact for students.